Dostop do raziskovalnih rezultatov - Češarek, Ana (Knjižnica, 2017)
Purpose: Requirements for open access of research results are expanding also to open access of research data that have been used as the base for scientific publication. In the digital environment, research data can become a valuable source if they are managed and preserved in an appropriate form, which enables them to be reused and shared. Print dissertations contain research data, which are often overlooked as they can be found in appendices. The purpose of our article is to find out what kind of research data do dissertation appendices contain. In addition, we wanted to compare our results with the results of a similar French research to check research data universality depending on geographical location and scientific discipline. Methodology/approach: The research is based on the assessment of 226 dissertation appendices from ten scientific disciplines (humanities and social science) submitted between 2010 and 2015 at the Faculty of Arts, the University of Ljubljana. We obtained the empirical evidence of what types of research data they contain regarding to the length, form, sources, and types as compared to a previous French research. Results: The results showed that 63% of dissertations contain appendices with some sort of research data; the appendices of different disciplines vary in the scope and data presentation types. The appendices within Archaeology and Art History are the most extensive, while the least extensive appendices can be found within Philosophy and Psychology. Practical implications: As the research results of dissertations are not easily accessible, we suggest that the university libraries offer assistance and advice to PhD students in managing their research data and help them publish in open repositories and open data archives. The university libraries have always played a vital role in preserving scientific communication. They will keep this role by managing, preserving and, therefore, providing easier access to research data as well.
Keywords: academic libraries; doktorati; doktorske disertacije; grey literature; odprti dostop; open access; raziskovalni podatki; research data; siva literatura; theses and dissertations; visokošolske knjižnice